MEMBUKA RUANG PARTISIPASI PEREMPUAN DALAM PEMBANGUNAN - Triana Sofiani (Muwazah, 2009)
It is a crucial matter for unchaining female participation scope in development when female themselves are always marginalized not only in the process but also the share of portion in development as well. This will give positive impact in order to amplify the quality of development application, especially which relates to female empowerment and gender. Hence, it may have high replication, not only in the impact of qualified family development but also in heaving female roles while taking decision. The next implication is to be able to encourage national development products in order to be well shared among males and females.